Drip irrigation systems in sandy soil using physical and hydraulic barriers - Zien El-Abedin, T.K.; Ismail, S. M.; Wassif, M. A.; El-Nesr, M. N. (2006)
A new method to barricade water deep percolation was investigated. This method was called 'The hydraulic barrier technique'. The method involves burying a secondary dripper line under the primary one in order to increase the deep layers' water content whereas to minimize matric potential in these layers. So that to increase the side movement of water from the primary dripper line. The method was validated by a field experiment in Sinai sandy soil. The field experiment tested four burying depths of primary dripper line, with and without the hydraulic barrier, compared with the physical barrier. Two crops were used, Jerusalem artichokes (Tartoufa) as example to tuber roots, and tomato as fibrous root. The results showed that the physical barrier extremely increased both crops more than double its normal in the absence of physical barrier value (2.35 for Tartoufa and 2.19 for Tomato), and the hydraulic barrier existence increased the total crop yield of Tartoufa by about 12% and marketable yield by 47%. Reduction of Tomato yield was found due to existence of hydraulic barrier by about 25%. The Tartoufa yield increased directly proportional to the burying depth of the primary lateral while the situation is inverted in the tomato. The hydraulic barrier acted the same like the physical barrier when the gap between the two dripper-lines getting narrower.
Includes references.
Summary in Arabic.
1
Keywords: Microirrigation; Water-power.; Sandy soils